Histopathological and histochemical changes in thyroid and liver during starvation in drug induced hypothyroid albino rats - Goyal, Meenakshi; Singh, Sukhdev; Roy, K S; Soni, G (The Indian Journal of Animal Sciences, 2005)
The present investigation was carried out to study the histopathological changes occurred due to thyroid malfunction and starvation in rats. Rats were divided into 4 groups. After inducing hypothyroidism in groups 2, 3 and 4 by administrating carbimazole (5 mg/d/100g bw) in feed for 22 days, the rats of groups 3 and 4 were kept on fast for 48 and 72 hrrespsctivcly. Group 1 taken as euthroid control. After sacrifice, the samples of thyroid and liver were fixed in 10% neutral buffered formalin for histopathological studies. Blood was collected for assessment of thyroid hormones.Included hypothyroid rats showed hypertrophy and hyperplasia ol'follicullar epithelium, devoid of colloid material and increased capillary network in thyroid gland as compared to euthyroid rat. Thyroid section of 48 and 72 hr starved hypothyroid rats. in addition to hypertrophied follicles, showed dialation and marked increase in the number of blood vessels. Severe necrotic changes were observed in hepatic tissues of 48 and 72 hr fasted induced hypothyroid rats.